The development of balanced literacy approach-based reading material for students of elementary school - Sutri Ekawati; Rukayah Rukayah; Kartika Chrysti Suryandari (Universitas PGRI Madiun, 2022)
This study aims to describe the development of teaching materials for reading comprehension of story texts with the perspective of a balanced literacy approach. It focuses more on describing the result of feasibility testing on the developed teaching material. The study's design is Research and Development, introduced by Borg and Gall. This study involved two experts in language learning and 11 elementary school students taken by purposive sampling. The research data was obtained from the results of the validation sheet taken by observing and implementing the teaching material. The data analysis technique used is the Gregory formula. The result of expert validation shows that the reading material is well-developed and categorized as ready to use. On the other hand, the trials on teaching material to the student result excellently, which means accommodating the students' needs. In conclusion, the developed reading material using a perspective of balanced literacy approach is not only feasible but also practical